2003
DOI: 10.1523/jneurosci.23-35-11015.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Caspase-Independent Neuronal Death: Energy Depletion and Free Radical Generation

Abstract: Cultured rat embryonic cortical neurons undergo apoptosis when treated with the topoisomerase-I inhibitor camptothecin. Pharmacological or molecular caspase inhibition prevents apoptosis, but the neurons still die in a delayed nonapoptotic manner. Here we examine the mechanisms leading to such caspase-independent death, focusing on events related to mitochondrial malfunction, which accompanies this delayed death. Given that mitochondria are the major source of ATP in primary neurons, we examined the cellular e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 62 publications
2
47
1
Order By: Relevance
“…It remains unclear whether Survivin plays a direct or indirect role in the DNA repair process; however, it is apparent that disrupting Survivin disrupts double-strand DNA repair capabilities of radiation-resistant GBM cells, thereby sensitizing these cells to radiation-induced cell death. It has been previously demonstrated that energy depletion plays an important role in caspase-independent neuronal cell death (Lang-Rollin et al, 2003). The present study also suggests that Survivin contributes to a hypermetabolic state in GBMs upon radiation expsosure, contributing to their radioresistant phenotypes.…”
Section: Role Of Survivin In Enhancing Radiation Resistancesupporting
confidence: 74%
“…It remains unclear whether Survivin plays a direct or indirect role in the DNA repair process; however, it is apparent that disrupting Survivin disrupts double-strand DNA repair capabilities of radiation-resistant GBM cells, thereby sensitizing these cells to radiation-induced cell death. It has been previously demonstrated that energy depletion plays an important role in caspase-independent neuronal cell death (Lang-Rollin et al, 2003). The present study also suggests that Survivin contributes to a hypermetabolic state in GBMs upon radiation expsosure, contributing to their radioresistant phenotypes.…”
Section: Role Of Survivin In Enhancing Radiation Resistancesupporting
confidence: 74%
“…In cell culture and animal models, tau phosphorylation can protect cells from apoptosis (Li et al, 2007). The delayed (nonapoptotic) neuronal death in the rTg4510 model may be similar to that observed in cultured neurons when delayed caspase-independent death is observed in cells treated with an apoptosis-inducing agent while caspases are inhibited (Lang-Rollin et al, 2003).…”
Section: Discussionmentioning
confidence: 77%
“…It is possible that this or a similar mechanism may play a role in the nonapoptotic death of DNA damaged neurons with inhibited p53 (Lang-Rollin et al 2003).…”
Section: Transcriptional Inhibition As a Trigger For P53-mediated Neumentioning
confidence: 99%